Word meaning - Hudson, Richard A. (Routledge, 1995)
Words and meanings. Senses and referents. Classification. Typicality. Definitions. Encyclopedias. Lexemes. Consistency. Arguments. Change. Humanity. Parents. Families. Verbs.